Learning path : Groovy. - Kousen, Ken; Safari eBooks ([Place of publication not identified] : O'Reilly Media, 2015)
"Groovy is a powerful, multi-faceted language for the Java platform that integrates smoothly with any Java program. In this Learning Path, you'll see how writing anything, from a simple build script to a full-scale application, is much easier with Groovy than with Java. Discover the many advantages of adding Groovy to projects written in Java and other object-oriented languages."--Resource description page.
Groovy programming fundamentals / with Ken Kousen -- Practical Groovy programming / with Ken Kousen -- Mastering Groovy programming / with Ken Kousen.
Title and publication information from resource description page (Safari, viewed March 14, 2016).
Presenter, Ken Kousen.
Keywords: Groovy (Computer program language); Electronic books